Vulvectomy for Vulval Cancer Using Triple Incision in a Low-resource Setting: A Case Report of a Young Immunocompromised Patient - Olanrewaju Saheed Jimoh; Muritala Sulaimon; Taofeek Ajani Ogunfunmilayo; Adewale Mukaila Alayo; Rofiat Temitope Lemboye-Bello; Nafiah Abolanle Taiwo; Igbo Amarachi Mary-Prudence; Sariyu Ibiyemi Olonade (Nigerian Journal of Medicine)
Vulval cancer is a rare gynaecological cancer usually affecting postmenopausal women, but the mean age of incidence is dropping due to the rising incidence of Human Papillomavirus (HPV) infection. Treatment of vulval cancer involves various options, including surgery, which should be tailored to each patient’s needs. The goal is to achieve a complete cure while opting for the most conservative approach possible. The case of a 34-year-old para 1 + 0 (1 alive) immunocompromised woman who had vulval cancer is reported. The patient presented with a four-year history of progressively increasing fleshy growth on the vulva with associated itching, ulcer and minimal bleeding. An initial suspicion of vulval carcinoma was entertained, and this was confirmed with a tissue biopsy. The patient subsequently had a vulvectomy and superficial inguinal lymphadenectomy using a triple incision with a good postoperative outcome. The psychological, physical and financial burdens of vulva cancer are enormous. While advancements in treatment have improved the outcomes of the disease, challenges remain in managing the advanced cases, and there is a need for continued research to enhance treatment effectiveness and improve the quality of life for affected women.